2005
DOI: 10.1111/j.1464-410x.2005.05294.x
|View full text |Cite|
|
Sign up to set email alerts
|

The role of urinary urgency and its measurement in the overactive bladder symptom syndrome: current concepts and future prospects

Abstract: OBJECTIVE To review the concept of urinary urgency and its practical measurement in clinical trials, and advance the hypothesis that while urge is experienced by normal people, urgency is always pathological. METHODS According to the International Continence Society (ICS) definition, urgency is the primary symptom of the overactive bladder (OAB) syndrome, but in clinical trials there are inconsistencies in both the definition and assessment of urgency. We searched the PubMed and BIOSIS databases for publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
177
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 23 publications
4
177
1
7
Order By: Relevance
“…According to the ICS terminology report, urgency is defined as 'the complaint of a sudden compelling desire to pass urine, which is difficult to defer' [3]. Although this definition appears clear at first sight, it seems to have inherent difficulties and has been the subject of numerous reports and communications [2,[4][5][6][7][8]. The main critics or questions are: is urgency a separate pathological sensation, or an extreme form of a normal sensation; does urgency always occur suddenly or can it result from a gradual build-up of sensation; is urgency one uniform sensation or do different types or grades of urgency exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the ICS terminology report, urgency is defined as 'the complaint of a sudden compelling desire to pass urine, which is difficult to defer' [3]. Although this definition appears clear at first sight, it seems to have inherent difficulties and has been the subject of numerous reports and communications [2,[4][5][6][7][8]. The main critics or questions are: is urgency a separate pathological sensation, or an extreme form of a normal sensation; does urgency always occur suddenly or can it result from a gradual build-up of sensation; is urgency one uniform sensation or do different types or grades of urgency exist.…”
Section: Discussionmentioning
confidence: 99%
“…The OAB syndrome is a highly prevalent condition in which urgency is considered the key symptom [2]. Therefore, a uniform generally accepted and correct description of the term urgency is indispensable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing the existing literature in 2005 Chapple and colleagues [5] showed that the methods of assessing urgency were deWcient in accuracy, largely unvalidated and inconsistent with the accepted ICS deWnition. Currently there is enormous controversy over the applicability and usefulness of the term 'urgency', particularly as its diVerentiation from urge does not translate into the majority of languages.…”
mentioning
confidence: 99%